Effects of Physiotherapeutic Scoliosis-Specific Exercise for Adolescent Idiopathic Scoliosis Cobb Angle: A Systematic Review - Hiroki Oba; Kei Watanabe; Tomoyuki Asada; Akira Matsumura; Ryo Sugawara; Shinji Takahashi; Haruki Ueda; Satoshi Suzuki; Toru Doi; Takumi Takeuchi; Hideyuki Arima; Yu Yamato; et al. (Spine Surgery and Related Research)
Background: The study of physiotherapeutic scoliosis-specific exercise (PSSE) for adolescent idiopathic scoliosis (AIS) is rapidly progressing. However, there are limited reports on the medium- to long-term effects of PSSE on scoliosis. Methods: A systematic review and meta-analysis feasibility study were conducted according to the Cochrane and Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. In our exhaustive search, we employed nine search formulas and four search databases according to a preregistered protocol. Identification, screening, eligibility, inclusion, and meta-analysis were performed through repeated meetings involving all coauthors. Each process was conducted by three or more authors. Results: A total of 1,518 studies were identified in the initial search. After manually reviewing abstracts and full texts, 11 studies were chosen for evaluation and reporting. The overall risk-of-bias was high in approximately half of the studies and moderate in the other half, with none found to have a low risk-of-bias. Only two randomized controlled trials (RCTs) specifically evaluated the therapeutic effect of PSSE on over a 1-year clinical course and the preventive ability of PSSE on surgery. One RCT reported that Cobb angle was substantially smaller in the PSSE group than in the control group at the final follow up, whereas the other found no significant difference between the groups. The methods of exercise intervention, control group selection, and timing of outcome assessments were not standardized in the selected studies. Thus, conducting a meta-analysis of the literature was deemed unfeasible at this time. Conclusions: The certainty of the evidence that PSSE reduces the progression of Cobb angle in patients with AIS in the short and long term was extremely low. Accordingly, healthcare providers should carefully examine the current evidence when explaining and applying PSSE in such patients. High-quality studies addressing the long-term changes in Cobb angle and Cobb angle at bone maturity as primary outcomes are warranted. Level of Evidence: Level 1